DESIGN AND IMPLEMENTATION OF AN ENERGY-EFFICIENT SMART WEATHER STATION USING IOT AND SENSOR TECHNOLOGY - Balami, Bwanthlala Yusuf; Ali, Danladi; Medugu, Dale W. (FUDMA JOURNAL OF SCIENCES, 2025)
The increasing demand for accurate and real-time weather data necessitates the development of innovative monitoring systems that emphasize energy efficiency and sustainability. This paper presents the modeling and development of a smart weather station using sensor technology, integrating a comprehensive array of meteorological sensors, a low-power microcontroller, and renewable energy sources. The process involved the design and simulation of the station using Proteus software, hardware implementation, prototype validation, and determination of power consumption. By employing low-power components, the system reduces energy usage while maintaining uninterrupted operation. The performance of the developed station was evaluated against the Davis Vantage Pro2 weather station, serving as the reference. Statistical analysis showed a strong correlation between both stations, with R² values exceeding 0.9, and relatively low root mean square error (RMSE), mean bias error (MBE), and mean absolute error (MAE), indicating reliable data accuracy. Power consumption tests revealed a consistent current draw of approximately 0.1663 A (0.84 W), significantly lower than typical full-featured commercial systems. This highlights its suitability for off-grid or remote environments where energy conservation is critical. This energy-efficient smart weather station contributes to more localized, responsive weather monitoring, particularly beneficial for agricultural planning, environmental studies, and climate research. Its integration of sustainable design and reliable performance demonstrates a practical approach to addressing meteorological monitoring challenges while advancing green technologies in environmental data acquisition.